Cutis 2022
DOI: 10.12788/cutis.0587
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Underrepresented in Medicine Applicant Backgrounds and Outcomes in the 2020-2021 Dermatology Residency Match

Abstract: Ms. Rinderknecht reports no conflict of interest. Dr. Brumfiel and Ms. Jefferson held leadership roles in the Dermatology Interest Group Association while work was being done on this study. Drs. Worswick and Rosman are dermatology residency program directors at their respective institutions and serve on the Association of Professors of Dermatology Residency Program Directors Section steering committee. Dr. Rosman also is the chair of the committee. These are elected positions without financial compensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…6 Soliman et al 7 found that racial minorities and lowincome students were more likely to cite socioeconomic barriers as factors involved in their decision not to pursue a career in dermatology. This notion was supported by Rinderknecht et al, 8 who found that Black and Latinx dermatology applicants were more likely to come from disadvantaged backgrounds, and Black applicants were more likely to indicate financial concerns as their primary reason for not pursuing an RF. The impact of accumulated student debt and decreased access should be carefully weighed against the potential benefits of an RF.…”
Section: U T I S D O N O T C O P Ymentioning
confidence: 81%
“…6 Soliman et al 7 found that racial minorities and lowincome students were more likely to cite socioeconomic barriers as factors involved in their decision not to pursue a career in dermatology. This notion was supported by Rinderknecht et al, 8 who found that Black and Latinx dermatology applicants were more likely to come from disadvantaged backgrounds, and Black applicants were more likely to indicate financial concerns as their primary reason for not pursuing an RF. The impact of accumulated student debt and decreased access should be carefully weighed against the potential benefits of an RF.…”
Section: U T I S D O N O T C O P Ymentioning
confidence: 81%
“…Lastly, given the uncertainty and anxiety associated with the pandemic, applicants may have preferred to stay in their current location where they presumably already have a support system and higher degree of stability. The changes in the “home” match rate are important to consider from an equity perspective, as previous data shows that UIM students are more likely to graduate from medical schools without home dermatology programs [ 17 ]. As the residency application landscape continues to change, it is important to consider how virtual interviews and away rotation policies impact geographic match trends and diversity in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of early exposure and research opportunities may pose barriers for UIM interested in dermatology. For example, matching into competitive specialties such as dermatology often requires several dermatology-specific publications and experiences; matched dermatology applicants had an average of 20.9 publications [ 5 ]. This may dissuade students who do not begin research early in their medical school careers from entering the field.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported a lack of group identity, noting the scarcity of role models who looked like them, and described the field as "overwhelmingly White" [ 3 ]. Applying to dermatology is costly due to the need to apply to many programs, research years, and away rotations, all of which pose financial barriers for UIM students or those from low-income backgrounds [ 2 , 3 , 5 ]. Additionally, the focus on the United States Medical Licensing Examination (USMLE) step scores and research has disadvantaged UIM students [ 2 ].…”
Section: Introductionmentioning
confidence: 99%